Hubungan Kecerdasan Intrapersonal dan Motivasi Belajar dengan Hasil Belajar Kognitif Fiqih Kelas XI MA Al-Hikmah (PRIMA) Kajen Margoyoso Pati - Nurul Huda; Nanang Nabhar Fakhri Auliya (JEID: Journal of Educational Integration and Development, 2021)
This study aims to achieve maximum cognitive learning outcomes of students. Student cognitive learning outcomes something that comes from students through the ability and encouragement in themselves. But in reality, students who have high intrapersonal intelligence and motivation to learn even cognitive learning outcomes are still the same. This research uses correlational quantitative research. In addition, this study used random sampling to determine the number of samples to be studied, namely 30 students in 4 classes. Collecting data using tests, questionnaires, documentation, observation and google form. Calculation of data analysis techniques using the help of SPSS for Windows 23 Version. The results of this study are as follows: (1) the level of intrapersonal intelligence of class XI students is categorized as being achieved by the respondent frequency of 23 students at intervals of 63 <X ? 88 with a percentage of 77%, (2) the level of learning motivation of class XI students. is known to be included in the high category achieved by the respondent frequency of 27 students in the interval X> 73 with a percentage of 88%, (3) the level of cognitive learning outcomes of class XI students is known to be in the high category achieved by the respondent frequency of 11 students at interval X> 88 with a percentage of 37%, and (4) there is a positive correlation between intrapersonal intelligence and learning motivation with the cognitive learning outcomes of class XI MA Al-Hikmah (PRIMA) Kajen Margoyoso Pati.